Raba tujk v mariborskih govorjenih medijih - Valh Lopert, Alenka (Slavia Centralis, 2020)
Use of foreign words in Maribor spoken mediaThis article examines the foreign words used by professional announcers in their prepared and non-prepared (spontaneous) speech on two radio stations in Maribor, the national broadcaster (Radio Maribor) and the commercial channel (Radio CITY). The analysis includes 34 speakers; the words were defined according to their etymology and their possible Slovene equivalents.
Keywords: Slovene language; Language of media; foreign words; Radio Maribor; Radio City